The process of negotiating and balancing digital play in everyday life: Adolescents’ narratives - Fiona M. Loudoun; M. Larsson-Lund; B. Boyle; A. Nyman (Scandinavian Journal of Occupational Therapy)
Background Everyday lives of adolescents reflects a pattern and balance of occupations across the awake-sleep continuum. Despite ongoing discussions regarding overconsumption, play in digital spaces is an occupation of choice for many adolescents.Aim To explore and identify how the meaning of playing video games is situated in adolescents’ everyday life.Material and Method Five participants aged 16–17 years were recruited. Data was generated through interviews and encounters using recorded clips of their play in digital spaces. Narrative analysis was utilised to explore the stories of adolescent’s digital play in everyday life.Results The overall plot of ‘bridging the divide’ represents and symbolises how play in the digital space is integrated in adolescents’ everyday life as they negotiate and balance the habits and routines of everyday life. Four storylines help demonstrate the stories told.Conclusion Playing in digital spaces enabled the participants to be part of an ongoing story where meaning could be negotiated and created. Play was interwoven in the complexity of routines reflecting the importance of examining the integrated whole of adolescents’ everyday life.Significance These findings are significant in shifting current assumptions and discourses of how digital play is situated in everyday life.